ANALISIS FAKTOR KEUANGAN DAN NON KEUNGAN TERHADAP UNDERPRICING SAHAM RETURN 7 HARI SETELAH IPO - Martha Carolina (Jurnal Akuntansi Bisnis, 2017)
The aim of this study is to determine the factors that affect the level of underpricing. The variables studied include finance leverage (FL), return on equity (ROE), the percentage of shares offered to the public (PSP), and underwriter reputation (UND). Initial Public Offering (IPO) is an initial public offering by an organization of the company to public investors through the capital market. Stock prices in the primary market and the secondary market is different, and therefore this difference will lead to a condition called underpricing and overpricing. Investors generally preferred the shares on the primary market because it provides initial return. Return indicates the underpricing of shares in the primary market when it entered the secondary market. Underpricing is a state in which the stock price at the time of the IPO lower than at the time traded on the secondary market.The research was conducted using multiple regression analysis. Data collected by observation techniques. The sample in the study were selected by purposive sampling method and obtain research samples as many as 65 companies that underpricing. The result of F test shows that significant value 0,051 (significant at α = 5%) . The result of t test shows that significant variable is underwriter reputation (UND) at significant value 0,0045; meanwhile finance leverage (FL), return on equity (ROE), and percentage of shares offered to the public (PSP) are not significant.The conclusion of this study are finance leverage (FL), the return on equity (ROE), the percentage of shares offered to the public (PSP) not proven effect on return 7 days after the IPO (R7hr), meanwhile underwriter reputation (UND) is proven effect negative return 7 days after the IPO for firms shares on The Stock Exchange having underpricing. The suggestion for this study is investor expected to pay attention to the information contained in prospectus, especially regarding underwriter reputation. Keywords: Underpricing, finance leverage (FL), return on equity (ROE), the percentage of shares offered to the public (PSP), and underwriter reputation (UND)